1979
DOI: 10.1136/bmj.1.6178.1591
|View full text |Cite
|
Sign up to set email alerts
|

Randomised comparison of methyldopa and oxprenolol for treatment of hypertension in pregnancy.

Abstract: Summary and conclusionsFifty-three pregnant women with moderately severe hypertension were randomly allocated to treatment with methyldopa or oxprenolol. There were no significant differences between the groups in age, height, weight, parity, or To examine the effects of antihypertensive treatment more closely and to evaluate alternative forms of treatment we conducted a randomised comparison of methyldopa and a non-selective beta-adrenoceptor-blocking drug, oxprenolol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(35 citation statements)
references
References 21 publications
1
34
0
Order By: Relevance
“…Thus the present group might be considered unsuitable for the assessment of efficacy of atenolol. There is no theoretical reason why atenolol should not be a suitable antihypertensive agent for pregnant patients, as has been the case for other ,8-adrenoceptor blockers such as oxprenolol (Gallery et al, 1979), propranolol (Eliahou et al, 1978), labetolol (Lamming & Symonds, 1979) and metoprolol (Sandstrom, 1978).…”
Section: Results (I) Pharmacokinetic Studymentioning
confidence: 99%
“…Thus the present group might be considered unsuitable for the assessment of efficacy of atenolol. There is no theoretical reason why atenolol should not be a suitable antihypertensive agent for pregnant patients, as has been the case for other ,8-adrenoceptor blockers such as oxprenolol (Gallery et al, 1979), propranolol (Eliahou et al, 1978), labetolol (Lamming & Symonds, 1979) and metoprolol (Sandstrom, 1978).…”
Section: Results (I) Pharmacokinetic Studymentioning
confidence: 99%
“…One of the studies found it necessary to add hydralazine to both treatment regimens of oxprenalol and methyldopa for improved blood pressure control. 16 Combination drug therapy confuses an already complex condition involving the mother and the foetus. The reported effects of antihypertensive drugs on the placental circulation and therefore oxygenation of the foetus are conflicting.…”
Section: Discussionmentioning
confidence: 99%
“…There is still confusion amongst clinicians concerning treatment and consequently the disease accounts for significant maternal and foetal mortality and morbidity. Despite the confusion recent reports show that control of hypertension in pregnancy by antihypertensive drugs results in better survival (Michael 1975;Redman et al, 1976;Michael, 1979a;Gallery et al, 1979).…”
Section: Introductionmentioning
confidence: 99%